PERILAKU PENGGUNAAN KONTRASEPSI PADA PUS SELAMA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS KUTA UTARA - Ni Made Rai Widiastuti; Ketut Novia Arini (LPPM Universitas Abdurrab, 2021)
Nationally, the results of family planning services during the COVID-19 pandemic, there was a decrease in the use of contraceptives reaching. This can cause various problems including an increase in the number of unwanted pregnancies (unwanted pregnancy) and baby booms or an increase in the birth rate. This study aims to determine how the behavior of contraceptive use among couples of childbearing age during the COVID-19 pandemic at the Primary Health Care North Kuta. This research is a survey research with cross sectional analytic research design. The population in this study were all fertile age couples (PUS) in Denpasar City and the number of samples used was 365 respondents with a purposive sampling technique. The results of this study found that most respondents are currently using contraception. Analysis of bivariate data with chi square obtained variables of age, parity, family income, perceived benefits, perceived barriers, availability of service places, and husband's support. Multivariate analysis with logistic regression found that husband's support variable has the most dominant influence on contraceptive use behavior.